THE EFFECT OF CROSSWORD TECHNIQUE ON STUDENTS’ VOCABULARY MASTERY - Rabi’ah Rabi’ah (E-LINK JOURNAL, 2018)
Having many vocabularies  is very important in learning English. Vocabulary is one of factors that determines the success of four English Skills. The students who have enough vocabulary could be easier in learning English. From this reason, the teacher should give a good technique to teach vocabulary. Crossword technique is one of an interesting, enjoyable, and fun that should be used by the teacher. Crossword technique is also effective in enrich students’ vocabulary. By implementing the crossword technique the students don’t feel memorizing the vocabularies, they could add their vocabulary unconsciously. This study is aimed to find the effect of crossword technique on students’ vocabulary mastery. It was done at MTs Miftahul Ulum Palengaan Pamekasan. The participant  is the seventh grade students. The total number of the participant is 20 students. This study was quantitative research and quasi experimental as the design. Vocabulary test was used to collect the data which consist of 50 questions. The form of test was multiple choice test. There were two tests, namely pretest and posttest. Pretest was done before giving treatment and posttest was done after giving treatment. To achieve the objective of this study the data were analyzed by using dependent t test with the help of SPSS 20. The result turned out to test the hypothesis which states students score in the posttest are different from their score in the pretest. The finding showed that the alternative hypothesis is accepted. It was proven by the result of computation of t-value is higher than critical 0.05 with df 19.It means that the alternative hypothesis (Hi) was accepted.  From those explanations above, it could be concluded that there is significant effect of crossword technique on the first grade students’ vocabulary mastery at MTs Miftahul Ulum Gunung Tangis Palengaan Pamekasan. Therefore, teaching vocabulary by using crossword technique was more effective than teaching vocabulary conventionally.From this finding, the researcher suggests for the English teacher to use crossword technique in teaching vocabulary because this technique is very enjoyable and interesting for the students. Moreover, for the institution who doesn’t have enough facilities.